Effects of acupuncture and Nordic walking practice, and their interaction, on bodily fluids distribution of breast cancer survivors - Andrea Di Blasio; Massimo Rinaldi; Teresa Morano; Pascal Izzicupo; Stefania Dell’aquila; Simona Grossi; Luca Russo; Marco Bergamin; Stefano Gobbo; Gianluca Viscioni; David Cruz-Díaz; Francesca Di Giandomenico; et al. (Human Movement, 2022)
Purpose Integrative treatments are growing among breast cancer survivors (BCS), and both acupuncture and Nordic walking (NW) are found particularly useful for them. Their positive effect on BCS health is partially due to their impact on bodily fluid balance. The study of bodily resistance and reactance is a practical method to monitor bodily fluid balance. The aims of our study were to investigate (a) the acute effects of acupuncture treatment on resistance and reactance in BCS who never had received acupuncture treatment before; (b) if BCS practising NW had better resistance and reactance than non-exercising BCS; and (c) if BCS practising NW presented a better response after acupuncture treatment than other conditions.